(untitled) (The Pakistan Development Review, 2009)
Syed Naveed Qamar, Federal Minister for Petroleum and Natural Resources, Dr Ishfaq Ahmad, Deputy Chairman, Planning Commission, Professor Syed Nawab Haider Naqvi, Former President, PSDE, Dr Sarfraz Khan Qureshi, Former President, PSDE, Dr G. M. Arif, Secretary, PSDE, Past Presidents and Distinguished Members of the Society. Excellencies, Ladies and Gentlemen It is my pleasure to welcome you all to the 25th Annual General Meeting and Conference of the Pakistan Society of Development Economists. We are extremely grateful to Syed Naveed Qamar, Federal Minister, Petroleum and Natural Resources, for having spared his precious time to join us at the inaugural session. It was during your tenure as Finance Minister that important and difficult economic decisions were taken to restore macroeconomic stability resulting from the unprecedented increases in international commodity prices, the global financial meltdown and neglect and inaction of past policy-makers. That the economy today has achieved macro stability in many of the key indicators is to a large measure the result of these decisions. I am also extremely grateful to our Patron Dr Ishfaq Ahmad, Deputy Chairman, Planning Commission, for his active interest and support to the work of our Society. A warm welcome to our members and guests who have come from different parts of the country and abroad. It is especially satisfying to see our future economists from all over the country join us at the Conference. Let me join Dr Arif in welcoming Dr Mohsin Khan who will be delivering the Quaid-i-Azam Lecture, Professor Hirashima who will be delivering the Allama Iqbal Lecture, Professor John Casterline, the Mahbubul Haq Lecture and Professor Robin Burgess, the Gustav Ranis Lecture (which we started last year).